The benefits of adipocyte metabolism in bone health and regeneration - Burkhardt, Lisa-Marie; Bucher, Christian H.; Löffler, Julia; Rinne, Charlotte; Duda, Georg N.; Geissler, Sven; Schulz, Tim J.; Schmidt-Bleek, Katharina (Frontiers in Cell and Developmental Biology, 2023)
Patients suffering from musculoskeletal diseases must cope with a diminished quality of life and an increased burden on medical expenses. The interaction of immune cells and mesenchymal stromal cells during bone regeneration is one of the key requirements for the restoration of skeletal integrity. While stromal cells of the osteo-chondral lineage support bone regeneration, an excessive accumulation of cells of the adipogenic lineage is thought to promote low-grade inflammation and impair bone regeneration. Increasing evidence indicates that pro-inflammatory signaling from adipocytes is responsible for various chronic musculoskeletal diseases. This review aims to summarize the features of bone marrow adipocytes by phenotype, function, secretory features, metabolic properties and their impact on bone formation. In detail, the master regulator of adipogenesis and prominent diabetes drug target, peroxisome proliferator-activated receptor γ (PPARG), will be debated as a potential therapeutic approach to enhance bone regeneration. We will explore the possibilities of using clinically established PPARG agonists, the thiazolidinediones (TZDs), as a treatment strategy to guide the induction of a pro-regenerative, metabolically active bone marrow adipose tissue. The impact of this PPARG induced bone marrow adipose tissue type on providing the necessary metabolites to sustain osteogenic- as well as beneficial immune cells during bone fracture healing will be highlighted.